Fabrication and Evaluation of Physically Crosslinked Stimuli Sensitive Polymeric Blend of Pva-Gelatin as Drug Delivery System by Freeze Thaw Cycles: Crosslinked Stimuli Sensitive Polymeric Blend by Freeze Thaw Cycles - Datta, Deepanjan; Bal, Trishna; Swain, Sabyasachi; Goswami, Sudipta (Iranian Journal of Pharmaceutical Sciences, 2018)
Vacuum dried Metronidazole hydrochloride (MTZ) loaded Crosslinked polymeric blend of Poly (vinyl) alcohol (PVA) and Gelatin (GE) in different ratios by 30 freeze/thaw cycles (FTC) tested for stimuli sensitivity and crosslinking at various pH, temperature, ionic concentration and oscillatory test along with dye absorption test showed maximum swelling in alkaline pH and decreased swelling with increased ionic concentration. Digital scanning calorimetry (DSC) thermo grams of the blank crosslinked sample showed a sharp endothermic peak at 160.57 0C and MTZ loaded samples showed two sharp endothermic peaks at 159.95 0C and 324.74 0C indicating the entrapment of drug in the polymeric network. Scanning electron microscopy (SEM) showed the rough polymeric texture. Fourier Transformation Infrared Spectroscopy (FTIR) confirmed the presence of new peaks in the cross-linked and drug-loaded sample. In-vitro drug release studies showed 98.253% ± 0.363 and 92.248% ± 0.244 releases in the first 6 hours. Biodegradability and bactericidal studies of the blank film indicated that the crosslinked sample is biodegradable and does not inhibit any microbial growth.